UJI POTENSI ANTIKOLESTEROL EKSTRAK ETANOL BUAH JAMBU BIJI MERAH (Psidium guajava L.) DENGAN METODE LIEBERMANN BURCHARD - Anggraini, Devina Ingrid (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2025)
The busy and hectic lifestyle of society leads people to often consume instant food. Instant foods that contain high levels of fat, cholesterol, and calories can trigger the occurrence of degenerative diseases, such as hypercholesterolemia, which is an increase in cholesterol levels in the blood. The compounds found in red guava fruit (Psidium guajava L.) include alkaloids, phenolics, saponins, and tannins, which are believed to help lower cholesterol levels. This study aims to evaluate the extract of red guava fruit as a cholesterol-lowering agent by measuring the EC50 value in vitro. The EC50 reduction activity was determined using the Lieberman-Burchard technique through UV-Vis spectrophotometry at a maximum wavelength of 669 nm. Extracts from red guava fruit were used at concentrations of 50, 75, 100, 125, and 150 ppm, respectively. This study reveals that the extract of red guava fruit shows anti-cholesterol activity at a concentration of 113.59 ppm.